THE CULTURAL AND RELIGIOUS DIMENSION OF THE FOREIGN POLICY OF RUSSIA AT THE TURN OF 17TH AND 18TH CENTURIES - A. V. Skizhenok (Vestnik MGIMO-Universiteta)
The author of this article aims to examine the role and place of the Russian Orthodox Church in Russia's transition from the regional state of the Middle Ages to an absolutist state of Modern history. Transformations in states' domestic and foreign policies that took place in Modern history cannot be reduced to a simple set of changes in various spheres of life of states, nations and peoples. By studying the transition from one type of statehood to another one we are dealing with a fundamental transformation of the entire state organism, the state as a cultural phenomenon, with a change in the very notion of what a state is and what its goals, objectives and functions are. The process of transformations in statehood affected all countries of the world including our Motherland. In Russia these changes had their own cultural and historical specificity which was largely formed by religiosity of our people and was rooted in the Orthodox faith. Therefore, the author considered it necessary to raise the question of how the cultural, historical and religious identity of the Russian people could influence the course of reforms in the sphere of the Russian state system in Modern history. The author focuses on the foreign policy of the Russian state built on cultural and religious values in I7th-I8th centuries. This foreign policy is seen as an alternative paradigm of the modern Russia's foreign policy. The author believes that the modern Russian state does not shape its foreign policy on the basis of core values of the Russian world view arising from the religious consciousness of our people. This fact deprives Russia’s foreign policy of unity with cultural and historical tradition of our state and in many respects weakens it. The article provides a possible answer to the question why a tendency to the framing of a foreign policy on the basis of values and religious outlook inherent in the Russian people did not prevail in the foreign policy of the Russian state.